IDENTIFIKASI KESALAHAN MATEMATIKA SISWA SMP BERDASARKAN TAHAPAN KASTOLAN - Raharti, Antonia Dwi; Yunianta, Tri Nova Hasti (Journal of Honai Math, 2020)
The study aims to identify kinds of high school students’ misrepresent in doing their tasks and to provide the appropriate scaffolding as a solution to help the students. This is a qualitative descriptive research. The research subject consists of three junior high school students who have different abilities in Mathematics. They were selected out of 92 students. This research studied the conceptual errors, procedural mistakes, and students’ technical mistakes in working on the problems based on the stages of Kastolan mistakes and the scaffoldings given. Furthermore, the data were collected by using the way of testing, interviewing and documenting techniques. The research data were guarantee validated with the triangulation method. The result of the research showed that there were some errors done by the students in doing the tasks. They were the conceptual errors, procedural mistakes, and technical errors. The scaffoldings given to help the students do the tasks for Level 1 (environmental provisions), Level 2 (explaining, reviewing dan restructuring), and Level 3 (developing conceptual thinking).